Foot - and Mouth Disease Syndrome in a Child. Due tc Coxsackie A16 Virus. - ΠΑΠΠΟΥΣ Χ.; ΜΠΡΟΒΑΣ Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
A virus from a male child, 4 years old, with Foot-and-Mouth Disease syndrome, that is vesicles on the tongue and toes, is isolated. This virus is lethal for unweaned mice, acid and resistant to chloroform as well as to 50° C for 30° in the presence of IM MgCl2. It does not grow in calf kidney monolayers and IBRS-2 cells. The virus was identified as Coxsackie, type AX6, using the serum neutralization test on mice, by the World Reference Laboratory (Pirbright- England). The authors express their gratitude to Drs J . Brooksby, H. Pereira and L. Buckley of the Animal Virus Research Institute at Pirbright for the typing of the virus abovementioned.